Impact of COVID-19 pandemic on screening and diagnosis of patients with prostate cancer: a systematic review protocol. Issue 8 (26th August 2022) - Mostafavi Zadeh, Seyed Mostafa; Tajik, Fatemeh; Moradi, Yousef; Kiani, Jafar; Ghods, Roya; Madjd, Zahra
Abstract : Introduction: With the exponential progress of patients with COVID-19, unexpected restrictions were directed to limit SARS-CoV-2 dissemination and imposed health-system an entire reformation to diminish transmission risk. These changes likely have caused the full range of cancer screenings and diagnosis gaps. Regardless of the recommendations, prostate cancer (PCa) screening/diagnosis programmes were momentarily postponed. Prostate-specific antigen (PSA) testing has been an inexpensive, low-invasive and relatively precise means of detection for PCa screening that would improve the uncovering of any type of PCa. Unfortunately, a decrease in PSA screening would significantly decrease PCa detection, with non-negligible growth in PCa-specific death. This review is designed to improve our understanding of the impact of the COVID-19 pandemic on the screening and diagnosis of patients with PCa. Methods and analysis: This systematic review will be reported in accordant with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidance. A comprehensive search has been executed through five main electronic databases: PubMed/MEDLINE, Web of Science, Scopus, Embase and ProQuest until 1 March 2022. Besides, grey literature, preprint studies and references of included studies will be searched. The main keywords have been used to perform the search strategy: COVID-19, prostatic neoplasms. All the relevant studies that met the inclusion criteria will be screened, selected and then extracted data by two independent authors. The quality assessment of the included studies will be performed by the Newcastle-Ottawa Scale. In case of any disagreement between the two authors in selecting, extracting data and assessing the quality of included studies, it will be resolved via consensus and checked by the third author. Ethics and dissemination: As this study will be a systematic review without human participants' involvement, there will be no requirement for ethics approval. Findings will be presented at conferences and in a peer-reviewed journal. PROSPERO registration number: CRD42021291656.